Technical Guidance for Oyster Mushroom Baglog Production Using a Semi-Mechanical Baglog Pressing in Poktan Turi Sidomulyo - Ayu, Putri Chandra; Mawarni, Lisa; Siregar, Luthfi Azis Mahmud; Siregar, Ameilia Zuliyanti; Lubis, Muhammad Charfi; Laksono, Muhammad Ridho (Talenta Publisher, 2023)
The Turi farmer group is located in Sidomulyo Village, Tuntungan, Medan. One of the businesses run by this group is the cultivation of oyster mushrooms. However, this poktan has not been able to produce oyster mushroom baglog independently. Thus, greater capital is needed to buy baglog from the manufacturer. Basically, the process of making oyster mushroom baglog is quite simple and can be conducted manually, but the common problems encountered are the long baglog production time, non-uniform quality and high number of workers. In addition, the production of oyster mushroom baglog can be used as another business by partner groups in an effort to increase the income of group members and cut production costs for oyster mushrooms in partner groups. The purpose of this activity was to improve the insight and skills of the community in the Turi Poktan to be able to produce the oyster mushroom baglog by utilizing a simple technology in the form of a baglog presser to cut the production costs and open up new business opportunities in order to improve the welfare of the community in partner Poktans. The expected results from this community service activity were products in the form of oyster mushroom baglog and the formation of a new business by the turi group as a producer of oyster mushroom baglog so as to increase the welfare of the community in partner groups.